2022
DOI: 10.3390/molecules27154692
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Bioisosterism Design, Synthesis, Biological Activity and Toxicity of 1,2,4-Oxadiazole Substituted Benzamides Analogues Containing Pyrazole Rings

Abstract: In order to discover pesticidal lead compounds with high activity and low toxicity, a series of novel benzamides substituted with pyrazole-linked 1,2,4-oxadiazole were designed via bioisosterism. The chemical structures of the target compounds were confirmed via 1H NMR, 13C NMR and HRMS analysis. The preliminary bioassay showed that most compounds exhibited good lethal activities against Mythimna separate, Helicoverpa armigera, Ostrinia nubilalis and Spodoptera frugiperda at 500 mg/L. Particularly in the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The results showed that compound 18 exhibited excellent larvicidal activity (100.0%) against mosquito larvae at 1 mg L −1 , but was less active toward M. separata , Helicoverpa armigera , and Pyrausta nubilalis at 500 mg L −1 . 58 Subsequently, a series of 1,2,4-oxadiazole derivatives were synthesized by incorporating the 3-ethyl-1-methyl-pyrazole-5-yl moiety derived from the insecticide tebufenpyrad. Analog 19 exhibited superior insecticidal activity against M. separata (70.0%) compared to tebufenpyrad (60.0%).…”
Section: 24-oxadiazole Derivatives With Pesticidal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that compound 18 exhibited excellent larvicidal activity (100.0%) against mosquito larvae at 1 mg L −1 , but was less active toward M. separata , Helicoverpa armigera , and Pyrausta nubilalis at 500 mg L −1 . 58 Subsequently, a series of 1,2,4-oxadiazole derivatives were synthesized by incorporating the 3-ethyl-1-methyl-pyrazole-5-yl moiety derived from the insecticide tebufenpyrad. Analog 19 exhibited superior insecticidal activity against M. separata (70.0%) compared to tebufenpyrad (60.0%).…”
Section: 24-oxadiazole Derivatives With Pesticidal Activitymentioning
confidence: 99%
“…1,2,4-Oxadiazole-substituted meta-benzamides were reported to exhibit a wide range of insecticidal activities, 58,59 but their fungicidal activities may have been overlooked. Inspired by this, several series of 1,2,4-oxadiazole-based benzamides were prepared by our group in 2021, 74 which aim to obtain diverse outcomes in order to expand the range of potential fungicide candidates.…”
Section: 24-oxadiazole Derivatives With Pesticidal Activitymentioning
confidence: 99%